Effect of oral creatine supplementation on single-effort sprint performance in elite swimmers - Burke, L. M.; Pyne, D. B.; Telford, R. D. (International Journal of Sport Nutrition and Exercise Metabolism, 1996)
Oral supplementation with creatine monohydrate (Cr.H2O) has been reported to increase muscle creatine phosphate levels. The aim of the present study was to determine the effect of such supplementation on performance of a single-effort sprint by elite swimmers. Thirty-two elite swimmers (M = 18, F = 14; age = 17-25 years) from the Australian Institute of Sport were tested on two occasions, 1 week apart. Tests performed were 25-m, 50-m, and 100-m maximal effort sprints (electronically timed with dive start, swimmers performing their best stroke), each with approximately 10 min active recovery. A 10-s maximal leg ergometry test was also undertaken. Swimmers were divided into two groups matched for sex, stroke/event, and sprint time over 50 m, and groups were randomly assigned to 5 days of Cr.H2O supplementation (4 . day-1 x 5 g Cr.H2O + 2 g sucrose, n = 16) or placebo (4 . day-1 x 5 g Polycose + 2 g sucrose, n = 16) prior to the second trial. Results revealed no significant differences between the group means for sprint times or between 10-s maximal leg ergometry power and work. This study does not support the hypothesis that creatine supplementation enhances single-effort sprint ability of elite swimmers.